Conversations with birds - Kumar, Priyanka, 1973- (Milkweed Editions, 2022)
""Birds are my almanac. They tune me into the seasons, and into myself." So begins this lively collection of essays by acclaimed filmmaker and novelist Priyanka Kumar"--